Left handed metamaterial incrporated with circular polarized microstrip antenna - Huda A. Majid, 1984-, author; Mohamad Kamal A. Rahim, author; T. Masri, author; International Symposium on Antenas & Propagation (2009: Bangkok, Thailand) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL